2020
DOI: 10.1002/cpsc.107
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Stability Testing of Pluripotent Stem Cells

Abstract: Pluripotent stem cell (PSC) cultures are subjected to selective pressures that can result in acquisition and expansion of recurrent genetic abnormalities at any time. These recurrent abnormalities enhance the variant cells harboring them with a competitive advantage over wild‐type cells. Variant cells can eventually supplant wild‐type cells entirely and become fixed in culture. Such variants can impact the efficacy of PSCs in research and clinical applications. Therefore, routine genomic characterization is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Importantly, accumulation of common chromosomal abnormalities should be closely monitored as aneuploidy (most frequently of chromosomes 12, 17, 20, and X) is common ( Assou et al., 2020 ; Taapken et al., 2011 ). At a minimum, G-banded chromosome analysis should be carried out immediately after iPSC derivation, after each cell expansion for banking, and after every 5–10 passages during culture ( Martins-Taylor et al., 2011 ; McIntire et al., 2020 ). In addition, a recent study has shown similar numbers of TP53 mutations in cells grown with and without feeder cells ( Merkle et al., 2017 ), but further studies are required.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, accumulation of common chromosomal abnormalities should be closely monitored as aneuploidy (most frequently of chromosomes 12, 17, 20, and X) is common ( Assou et al., 2020 ; Taapken et al., 2011 ). At a minimum, G-banded chromosome analysis should be carried out immediately after iPSC derivation, after each cell expansion for banking, and after every 5–10 passages during culture ( Martins-Taylor et al., 2011 ; McIntire et al., 2020 ). In addition, a recent study has shown similar numbers of TP53 mutations in cells grown with and without feeder cells ( Merkle et al., 2017 ), but further studies are required.…”
Section: Main Textmentioning
confidence: 99%
“…Clump passaging and avoidance of enzymatic dissociation when culturing iPSCs is advisable, as dissociation to single cells may select for the best adapted cells, contributing to genomic variation ( Bai et al., 2015 ; Garitaonandia et al., 2015 ). It is also advisable to track each line's passage number and avoid working with lines at >40 passages when aneuploidy and other mutations are more likely to arise ( Martins-Taylor et al., 2011 ; McIntire et al., 2020 ; Taapken et al., 2011 ). For this reason, it is crucial to expand and cryopreserve large numbers of vials of working stocks at low passage number for each iPSC line.…”
Section: Main Textmentioning
confidence: 99%
“…To decrease the costs of routine genome monitoring of several hPSC lines, one could first focus on excluding the presence of genetic aberrations that are known to occur with higher frequency in cultured hPSCs (Kuijk et al, 2020). The identification of recurrent abnormalities can be performed using fluorescence in situ hybridization (FISH) or quantitative polymerase chain reaction (qPCR) (McIntire et al, 2020). In addition, digital PCR has been suggested as a cost-effective and sensitive approach for the routine genome monitoring of hPSCs (Assou et al, 2020).…”
mentioning
confidence: 99%